Respuesta :

I believe it is either the first or last one, i hope this narrows down some answers

Odd function by definition has the property:

[tex] f(-x)=-f(x) [/tex]

Thus, we can immediately rule out all even powers of x. Now, we are left with the second and the last option. We can rule out the second option too because [tex] f(x)=4x^3+7 [/tex] and thus,

[tex] f(-x)=-4x^3+7 \neq-f(x) [/tex]

Now, the last option is: [tex] f(x) = 6x^3 + 2x [/tex]

[tex] \therefore f(-x) = 6(-x)^3 + 2(-x)=-6x^3-2x=-(6x^3 + 2x)=-f(x) [/tex]

[tex] \because f(-x)=-f(x) [/tex], therefore, the function in the last option is an odd function.